Resiliência, qualidade de vida e bem-estar espiritual em pessoas vivendo com hiv/aids - Santos., Saionara Ferreira Araújo dos (2011)
The Acquired Immunodeficiency Syndrome or AIDS, known by the acronym AIDS (Acquired Imunodeficiency Syndrome), is increasingly considered a major public health problem in the world scenario in view of its gravity and its character pandemic. The emotional care of patients with HIV / AIDS is of paramount importance to improve their quality of life but also his family. However, to conduct our analysis we assumed that emotional care is the ability to perceive the imperceptible, requiring a multidisciplinary team of high level of sensitivity to interpret verbal and nonverbal client to express their individual needs. Thus objectives of this study were to investigate whether religiousness-spirituality contributes to the process of resilience, quality of life and spiritual well-being for HIV / AIDS and can be considered a protective factor and also examines the issues that religious / spiritual facilitate the development of health interventions. This is an exploratory descriptive study with quantitative and qualitative approach, held in a federal public reference hospital in the city of João Pessoa. Protagonists of this study were 120 people. Data collection occurred from January to July 2011 and to make it viable three instruments were used type questionnaire, addressing the religious, the quality of life and level of resilience of the protagonists. In addition, we used an interview guide containing questions relevant to the proposed objectives. Regarding the analysis of data, quantitative grouped and tabulated in Excel and analyzed using statistical and presented in the form of tables with absolute numbers and percentages and qualitative data were analyzed according to the technique of content analysis. It was found that 85% of the protagonists of the study were male and 15% female, with age in both sexes ranging from 19 to over 60 years. It was also observed that 50% of both sexes were married. The fans were great predominance of religions rooted in Christianity, 45% and 21.67% of Catholics and Protestants. The majority of respondents belong to the black race, 59.1%, 17.8% said they were illiterate and / or literate. Some players said that the meaning of their lives is found in the "gods" and / or others, like the children, while other stakeholders understand the real meaning of their lives are their own lives, their own " I ", their existence and / or subexistência is the focus of their daily struggles. Thus, one can see how important and relevant issues, religious / spiritual acceptance and commitment from these individuals, to combat HIV / AIDS. The study met the proposed objectives and will certainly contribute to the assistance that group, since it will enable professionals involved in caring for clients that meet and outline strategies that contribute to improving the quality of life and spiritual welfare of those. Also, will contribute to further research in this area.